Experiences and health care preferences of women with ovarian cancer during the diagnosis phase. Issue 2 (3rd January 2019) - Jelicic, Lebecca; Brooker, Joanne; Shand, Lyndel; Knight, Tess; Ricciardelli, Lina; Denham, Geoff; Burney, Sue
Abstract: Objective: An ovarian cancer diagnosis presents physical and psychological challenges. Usually identified at an advanced stage, the disease involves invasive treatment and has a high mortality rate. The diagnosis phase is generally a time of heightened distress. Accordingly, the aim of this qualitative study was to explore the health care experiences and preferences of women with ovarian cancer during this phase, and identify opportunities to enhance women's experiences and outcomes. Methods: Thirty‐four women diagnosed with ovarian cancer were recruited from across Australia (median age = 60.5 years, range = 31‐74 years). Semistructured interviews explored participants' experience of health care services and preferences during the diagnosis phase. Thematic analysis of interview transcripts followed. Results: Five themes were identified including "navigating uncertainty" which summarized women's general experiences throughout the diagnosis phase and provided a context for concomitant health care preferences. Four other themes highlighted significant areas where health care may be better aligned with women's preferences. These included "responsiveness in health care, " "relational communication, " "person‐centered information, " and "preparation for living beyond cancer treatment." Conclusions: Responsive and prompt health care services that employ relational communication, provide patient‐centered information, and prepare women for survivorship could improve the health care experiences of women diagnosed with ovarian cancer.